2015
DOI: 10.1186/s12933-015-0248-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a preparation of minerals, vitamins and trace elements on the cardiac gene expression pattern in male diabetic rats

Abstract: BackgroundDiabetic patients have an increased risk of developing cardiovascular diseases, which are the leading cause of death in developed countries. Although multivitamin products are widely used as dietary supplements, the effects of these products have not been investigated in the diabetic heart yet. Therefore, here we investigated if a preparation of different minerals, vitamins, and trace elements (MVT) affects the cardiac gene expression pattern in experimental diabetes.MethodsTwo-day old male Wistar ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…As described previously, rats were fasted overnight (12 h) prior to serum glucose level measurements and OGTTs (weeks 7, 11 and 15) to verify the development of hyperglycemia and glucose-intolerance as diagnostic criteria of diabetes mellitus [ 21 , 22 , 36 ]. Blood samples were collected from the saphenous vein.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described previously, rats were fasted overnight (12 h) prior to serum glucose level measurements and OGTTs (weeks 7, 11 and 15) to verify the development of hyperglycemia and glucose-intolerance as diagnostic criteria of diabetes mellitus [ 21 , 22 , 36 ]. Blood samples were collected from the saphenous vein.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that cardiac gene expression pattern is significantly altered in obese ZDF rats, a model of T2DM and metabolic syndrome [ 21 ], and in streptozotocin-induced T1DM rats [ 22 ] at the transcript level. The effect of non-obese T2DM on gene expression pattern in various tissue types has been investigated in a few studies.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of extracellular matrix proteins, in particular collagens is one of the key processes in DCM. Sárközy et al have shown an altered expression of several genes related to cardiac hypertrophy and remodeling [ 41 ]. Minerals, vitamins, and trace elements treatment in diabetic rats resulted in opposite gene expression changes, showing beneficial effects in DCM [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sárközy et al have shown an altered expression of several genes related to cardiac hypertrophy and remodeling [ 41 ]. Minerals, vitamins, and trace elements treatment in diabetic rats resulted in opposite gene expression changes, showing beneficial effects in DCM [ 41 ]. In the present study enhanced nitro-oxidative stress and apoptosis in the diabetic myocardium, and a high histopathological cardiac fibrosis score were shown in accordance with the literature, and were proven to be normalized by a Zn(ASA) 2 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Selenium (Se), a trace element, is a key component of selenoproteins involved in a wide range of functions, including redox homeostasis, inflammatory regulation, thyroid hormone metabolism, immunity, myocardial and tumoral diseases, and reproduction [ 3 6 ]. Moreover, it is well documented that Se is associated with glucose metabolism, and both over supplementation and deficiency of Se can be associated with type 2 DM (T2DM) risk, following a U-shaped curve [ 3 , 7 , 8 ]. Selenoproteins are important metabolites of dietary Se, fulfilling the catalytic effects of Se, and are characterized by a selenocysteine (Sec), a selenium-containing amino acid encoded from the stop codon UGA in the molecular structure [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%